Effect of Palm Kernel Shell Ash Supplement with Egg Shell Ash on Stabilized Lateritic Soil for a Road Work - Sulaiman Olayinka Subair (ABUAD Journal of Engineering Research and Development)
Lateritic soil serves as a fundamental material in road construction; however, its engineering properties can be significantly improved through the use of additives. In Nigeria, the abundant generation of agricultural by-products—such as palm kernel shells, eggshells, and wood residues—presents challenges related to waste disposal and management. These materials can contribute to environmental degradation, including air and water pollution, and adversely affect local ecosystems. This study explores the effects of Palm Kernel Shell Ash (PKSA) and Egg Shell Ash (ESA) on the stabilization of lateritic soil for use in road pavement applications. Comprehensive geotechnical testing was conducted on natural lateritic soil to assess various parameters: Specific Gravity (SG), percentage passing sieve No. 200 (F-200), Liquid Limit (LL), Plastic Limit (PL), Plasticity Index (PI), Maximum Dry Density (MDD), Optimum Moisture Content (OMC), and both unsoaked and soaked California Bearing Ratio (CBR). These parameters were also measured for stabilized soil samples incorporating 4% PKSA and varying percentages of ESA (0%, 2%, 4%, 6%, 8%, and 10%) by dry weight of the lateritic soil, in accordance with West African Standards (WAS). The analysis revealed that the natural lateritic soil exhibited an SG of 2.53, F-200 of 27.00%, LL of 29.00%, PL of 17.20%, PI of 11.8%, MDD of 1820 kg/m³, OMC of 11.5%, and CBR of 22%. Conversely, the stabilized samples demonstrated SG values ranging from 2.3 to 2.5, F-200 between 27% and 28%, LL from 27.0% to 30.0%, PL between 10.0% and 17.2%, PI ranging from 10.3% to 11.8%, MDD between 1860 and 2000 kg/m³, OMC values between 8% and 11%, and CBR results from 25% to 80%. Notably, the combination of 4% PKSA and 8% ESA resulted in significant improvements in the engineering properties of the soil, rendering it suitable for use as sub-base material in road construction. Therefore, this blend is recommended for effectively stabilizing lateritic soil for road infrastructure projects.